IMPLEMENTASI MODEL PROJECT BASED LEARNING DALAM PEMBELAJARAN MUSIK ANGKLUNG DI SMP NEGERI 11 SEMARANG - Karina Dwi Novita Sari; Antonius Edi Nugroho; Siti Aesijah (STKIP Subang, 2026)
Learning Angklung music demands hands-on skills, teamwork, and precise musicality, thus requiring an engaging student-centered teaching approach. This research investigates the application of the Project Based Learning model in Angklung music classes at SMP Negeri 11 Semarang. It adopts a qualitative descriptive approach, involving the cultural arts teacher and Class VIII H students as subjects. Data collection involved observation, interviews, and documentation, validated via triangulation. Analysis followed Miles and Huberman’s framework: data gathering, reduction, display, and conclusion drawing. Findings reveal that Project Based Learning was executed in phases: selecting the project as an Angklung performance, planning with group and song allocations, progressive group rehearsals, and final ensemble presentations. Assessment covered rehearsal processes and performance results. The outcome was a polished Angklung ensemble emphasizing tempo, rhythm, and pitch accuracy. This model boosted student engagement, collaboration, accountability, and musical proficiency. Recommendations include teachers adopting Project Based Learning as an alternative, schools expanding Angklung instrument supplies, and students improving practice discipline for superior results.